Neonatal and pediatric respiratory care - Walsh, Brian K; Walsh, Brian K. (St. Louis, Missouri : Elsevier, 2019)
Learn to improve the respiratory care of neonates, infants, and children. Neonatal and Pediatric Respiratory Care, 5th Edition gives you a solid foundation in the assessment and treatment of respiratory disorders. Clear, full-color coverage simplifies the principles of respiratory care while emphasizing clinical application. A critical piece in respiratory care's total curriculum solution, this new edition includes all the changes in current clinical practice and in the education environment. Learning objectives at the beginning of each chapter break down key content into measurable behaviors, criteria, and conditions, and self-assessment questions provide an excellent review for the NBRC Neonatal/Pediatric Specialty exam.
I: Fetal development assessment, and delivery -- Fetal lung development -- Fetal gas exchange and circulation -- Antenatal assessment and high-risk delivery -- II: Assessment and monitoring of the neonatal and pediatric patient -- Examination and assessment of the neonatal and pediatric patient -- Pulmonary function testing and bedside pulmonary mechanics -- Radiographic assessment -- Pediatric flexible bronchoscopy -- Invasive blood gas analysis and cardiovascular monitoring -- Noninvasive monitoring in neonatal and pediatric care -- III: Therapeutic procedures for treatment of neonatal and pediatric disorders -- Oxygen administration -- Aerosols and administration of inhaled medications -- Airway clearance techniques and hyperinflation therapy -- Airway management -- Surfactant replacement therapy -- Noninvasive mechanical ventilation and continuous positive pressure of the neonate -- Noninvasive mechanical ventilation of the infant and child -- Invasive mechanical ventilation of the neonate and pediatric patient -- Administration of gas mixtures -- Extracorporeal membrane oxygenation -- Pharmacology -- Thoracic organ transplantation -- IV: Neonatal and pediatric disorders: presentation, diagnosis, and treatment -- Neonatal pulmonary disorders -- Surgical disorders in childhood that affect respiratory care -- Congenital cardiac defects -- Pediatric sleep-disordered breathing -- Pediatric airway disorders and parenchymal lung diseases -- Asthma -- Cystic fibrosis -- Acute respiratory distress syndrome -- Shock -- Pediatric trauma -- Disorders of the pleura -- Neurological and neuromuscular disorders -- V: Neonatal and pediatric transient and ambulatory care -- Transport of infants and children -- Home care -- Quality and safety.
Includes bibliographical references and index.
Keywords: Pediatric respiratory diseases; Perinatology; Respiratory Tract Diseases -- therapy; Infant, Newborn; Child; Respiratory Tract Diseases -- diagnosis; Respiratory Therapy -- methods; Fetal Development -- physiology; Pediatric respiratory diseases; Perinatology